Relative preferences for soil conservation incentives among smallholder farmers: Evidence from Malawi - Marenya, Paswel; Smith, Vincent H.; Nkonya, Ephraim M. (Wiley, 2014)
This paper uses framed choice experiments to examine the preferences of smallholder farmers in Malawi regarding alternative policy‐based incentives to adopt conservation practices that reduce soil erosion and increase yields. The policy incentives offered in the choice experiments included an ideal index‐based crop insurance contract, an index insurance contract with basis risk, cash payments, and fertilizer subsidies. Prior to implementing the choice experiments, the farmers participated in a workshop utilizing small group‐based dynamic learning games that demonstrated how index‐based crop insurance contracts function. The choice experiment results indicate that most farmers preferred cash payments to index insurance contracts, even when the insurance contracts offered substantially higher expected returns. Further, more risk averse farmers were more likely to prefer cash payments than less risk averse and risk loving farmers.